THE DIFFERENCE EFFECTIVENESS OF RUNNING HIGH INTENSITY INTERVAL TRAINING COMPARED WITH JUMP ROPE EXERCISE TO DECREASE BODY FACE PERCENTAGE IN ADOLESCENT WITH OVERWEIGHT IMT CATEGORY IN DENPASAR - Kurniawan, Mohammad; Wahyuni, Nila; Adiputra, uh Made Indah Sri Handari (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 2 (2018): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT One of the many health problems experienced by teenagers and experiencing a significant increase in terms of numbers each year is Overweight and Obesity. Overweight and obesity conditions can be handled by increasing physical activity in the form of running high intensity interval training and Jump rope exercise. The research was randomized pre and post control group design with sample of 15-18 year old teenagers amounted to 20 people and divided into two groups namely group running high intensity interval training and Jump rope exercise. Samples that met inclusion and exclusion criteria were randomized and then measured fat percentage using Bioelectrical Impendance Analysis (BIA). After 3 days of training a week for 4 weeks the sample is measured again for the data analysis. The result using Paired sample T-test to analyze that the group running high intensity interval training had p = 0,001 (p <0,05) and jump rope exercise had p = 0,003 (p <0,05) which mean in each group There was a significant decrease in fat percentage during and before training. Then the two groups were tested using Independent sample T-test with p p = 0,771 (p> 0,05), meaning there was no significant difference of effectivity in both groups. Key words: Adolescent, Overweight, Fat Percentage, Running High Intensity Interval Training, Jump Rope Exercise.